Large nested variant of urothelial carcinoma: a clinicopathological study of 36 cases. Issue 5 (14th August 2017) - Compérat, Eva; McKenney, Jesse K; Hartmann, Arndt; Hes, Ondrej; Bertz, Simone; Varinot, Justine; Brimo, Fadi
Abstract : Aims: The large nested variant of urothelial carcinoma (LNUC) has been added to the World Health Organization (WHO) 2016 classification. Scant data exist, and little is known about its clinical behaviour. Material and results: Cases fulfilling the morphological criteria of LNUC were collected. Pure and mixed cases (i.e. with other patterns of invasive UC) were studied. Immunohistochemical staining with cytokeratin (CK)7, p63, GATA‐3, CK20, p53 and Ki‐67 was performed. Included were 26 cystectomies (RC) and 10 resections (TURB) belonging to 36 patients with an average age of 66.7 years. Fourteen (39%) were pure LNUCs, and 22 (61%) displayed mixed features. Seventy per cent of the TURBs had pT2 tumours, while 58% of RCs had extravesical disease (≥pT3 and/or ≥pN1), with the rate of advanced disease being higher in mixed (69%) in comparison to pure cases (40%). Similarly, 38% of mixed cases had nodal metastases in comparison to 20% of pure cases. Overall, eight patients (24%) died of disease at a mean interval time of 21.7 months and seven patients (21%) showed recurrence or metastases. Disease progression was significantly higher in mixed cases (55 and 31% in mixed and pure cases, respectively). Positive staining was: CK7 = 87.5%, CK20 = 72%, GATA‐3 = 91%, P63 = 100%, p53 = 56% and Ki‐67 = mean of 16%. Conclusion: Despite the bland cytological appearance and deceptive pattern of invasion of the LNUC, our study validates its fully malignant potential with metastatic spread and tumour‐related deaths. Distinguishing mixed from pure LNUCs seems to be of value. LNUCs show comparable immunophenotype to both conventional urothelial carcinoma and the nested variant of urothelial carcinoma.